Business model patterns for 3D printer manufacturers. Issue 6 (13th June 2019) - Holzmann, Patrick; Breitenecker, Robert J.; Schwarz, Erich J.
Abstract : Purpose: The purpose of this paper is to analyze the business models that 3D printer manufacturers apply to commercialize their technologies. The authors investigate these business models and analyze whether there are business model patterns. The paper describes the gestalt of the business model patterns and discusses differences and similarities. Design/methodology/approach: The authors review the literatures on business models and 3D printing technology. The authors apply a componential business model approach and carry out an in-depth analysis of the business models of 48 3D printer manufacturers in Europe and North America. The authors develop a framework focusing on value proposition, value creation and value capture components. Cluster analysis is used to identify business model patterns. Findings: The results indicate that there are two distinct business model patterns in the industry. The authors termed these patterns the "low-cost online business model" and the "technology expert business model." The results demonstrate that there is a relationship between business model and technology. The identified patterns are independent of age, company size and country of origin. Research limitations/implications: The empirical results complement and extend existing literature on business models. The authors contribute to the discussion on business models in the context of novel technology. The technology seems to influence the gestalt of the business model. The sample is limited to European and North American companies and the analysis is based on secondary data. Originality/value: This is the first empirical study on the business models of 3D printer manufacturers. The authors apply an original mixed-methods approach and develop a framework that can function as a starting point for future research. 3D printer manufacturers can use the identified business model patterns as blueprints to reduce the risk of failure or as a starting point for business model innovation.